Mudanças e permanências na disciplina de biologia: o processo de implementação da base nacional comum curricular na rede estadual de ensino de São Paulo - Silva, Viviane Oliveira (2021)
Recent years have been characterized by a broad context of educational reforms, specifically curricular. Among curricular reforms, emphasis should be given to the elaboration of the National Common Curricular Base (BNCC) and its implementation, starting in 2018. The object of investigation of this study consists of the biology curriculum, organized by the São Paulo State Department of Education Paulo (SECUC-SP), for schools in the state education network of São Paulo. We mainly deal with the changes that occur in the biology curriculum, due to the implementation, the network mentioned above, and the principles and guidelines defined by the BNCC. Our research problem was formulated as follows: what changes occurred in the São Paulo State Curriculum, highlighting the discipline of biology, in the face of the process of implementing the BNCC? The objectives of the research were to investigate the changes that BNCC presents in the organization and content of the Biology discipline and to analyze how the changes defined by BNCC for that discipline are incorporated in the documents, which define the Official Curriculum of São Paulo. The research sources were the three versions of the BNCC and the documents, which define the organization of the school curriculum, for schools in the state education network of São Paulo. The investigation allowed us to conclude that in relation to the biology curriculum of SEDUC-SP, directly, analyzing and comparing the curricular documents produced since the 1980s, it can be observed that the contents or themes, which make up the curriculum, do not underwent changes, that is, what was taught to students in the state public system of São Paulo, in the biology curriculum component, will continue to be taught. The changes occurred in the general structure of the curriculum and not, explicitly, in the contents of the discipline.